Beyond a Construction Site, Beyond National Citizenship: The Infrapolitics of Translocal Citizenship - Vodovnik, Žiga (Two Homelands, 2012)
Since the nation-state ceases to exist as the only centre of sovereignty and arena where key political decisions are made, efforts to envisage new forms of citizenship are separating political membership from the nation and constitute it according to entirely new criteria. The article examines the new concept of translocal citizenship that moves away from the nation-state as its territorial reference point, and simultaneously rejects its continuation within some new supranational entity. In the second part, the article reflects on the Beyond a Construction Site project, initiated by the Obrat Culture and Art Association (KUD Obrat), where an unused construction site has been employed as a community garden. The project illustrates translocal citizenship in practice, since the garden is fostering new forms of collective action and new forms of political membership which are better suited to intercultural dialogue and inclusion of migrant communities than are nation-states.